An end to consensus? The selective impact of corporate law reform on financial development - Deakin, Simon; Sarkar, Prabirjit; Singh, Ajit (Brussels, 2011)
"Legal origins theory suggests that law reform should have a causal impact on financial development. We use recently created datasets measuring legal change over time in a sample of 25 developing, developed and transition countries to test this claim. We find that increases in shareholder protection contribute to stock market growth in the common law world and in developing countries, but not in the civil law world. We also find evidence of reverse causation, with financial development triggering legal changes in the developing world. We consider a number of reasons for the selective impact of law reform, focusing on the endogeneity of the legal system to its economic context, and on resulting complementarities between legal and financial institutions. "